Attenuation of the Aggregation and Neurotoxicity of Amyloid‐β Peptides by Catalytic Photooxygenation1. Issue 5 (11th December 2013) - Taniguchi, Atsuhiko; Sasaki, Daisuke; Shiohara, Azusa; Iwatsubo, Takeshi; Tomita, Taisuke; Sohma, Youhei; Kanai, Motomu
Abstract Alzheimer's disease (AD), a progressive severe neurodegenerative disorder, is currently incurable, despite intensive efforts worldwide. Herein, we demonstrate that catalytic oxygenation of amyloid‐β peptides (Aβ) might be an effective approach to treat AD. Aβ1–42 was oxygenated under physiologically‐relevant conditions (pH 7.4, 37 °C) using a riboflavin catalyst and visible light irradiation, with modifications at the Tyr10, His13, His14, and Met35 residues. The oxygenated Aβ1–42 exhibited considerably lower aggregation potency and neurotoxicity compared with native Aβ. Photooxygenation of Aβ can be performed even in the presence of cells, by using a selective flavin catalyst attached to an Aβ‐binding peptide; the Aβ cytotoxicity was attenuated in this case as well. Furthermore, oxygenated Aβ1–42 inhibited the aggregation and cytotoxicity of native Aβ.